A Study on Indoor Air Quality (IAQ) of University Libraries in Malaysia - Ja'afar, Nurul Aina Shasha; Abdul Wahid, Abdul Zaki (Progress in Engineering Application and Technology, 2021)
Indoor Air Quality (IAQ) refers to the level of air quality within and around buildings and structures where it related to the health and comfort of the buildings occupants and recently libraries have also been considered as a sick building syndrome and sick library syndrome has been identified. The goals of research to study field work methods used by previous studies of IAQ on university libraries in Malaysia and analysis perusal of physical parameter (temperature, air speed and relative humidity) and chemical parameters (carbon dioxide and carbon monoxide). The method used was data collection from the journal publication and compared with ICOP 2010, ASHRAE-62.1(2016) and ASHRAE-55 (2017). Based on the results obtained, the correlation studies shows that the outdoor environments do give impacts on the indoor air quality in the libraries as the libraries located in suburban area where background was busy in traffic and industrial factories. The libraries in suburban area shows the elevated on average temperature, CO2 concentration approaching maximum level and insufficient humidification. This correlation studies shows that the outdoor environments do give impacts on the indoor air quality in the libraries.